The Markets for the Ordo Liberal Concepts and Market Competition - Piotr WALĄG (Communications of International Proceedings, 2020)
The last decades of development of world economies have been marked by the transition to highly productive economies. The reasons for this state of affairs are mainly seen in the intensification of competitive forces in individual markets1, which force the introduction of new technologies and innovations. In view of this, it makes sense to ask what economic conditions are most conducive to strengthening the forces of market competition. The concept of competitiveness of economies is used to assess their economic condition and is analysed by looking for ways to achieve the highest possible levels of position and competitive ability. The competitiveness of an economy is determined by the strength of competition in its individual departments and branches. However, it is in the nature of economic entities to avoid the conditions in which they must be subject to the requirements of competition and to look for opportunities to benefit from a pension. The pursuit of the pension, however, lowers the productivity of the operation of the managing entities and makes the allocation of production resources sub-optimal. In conditions where none of the operating entities can take advantage of the market advantage, competition is born which forces continuous productivity growth. Otherwise, higher productivity is the result of competition, which eliminates the possibility of achieving a pension and forces a quick and effective reallocation of resources, as well as the search for and introduction of new technologies and innovations.  In Ordo liberal concepts, economic governance is subordinated to the material purpose of management as well as to overarching social values. The ideas of ordo liberal, which are at the heart of the social market economy, constitute the freedom of the individual in social and economic life, which is achieved under conditions in which the decisions and actions of individual individuals give shape to economic processes. Securing economic freedom is achieved in a constructivist approach to creating a competitive economic order. Competitive economic order aims at creating conditions and securing full competition between entities, where economic profitability is achieved only as a result of increasing / increasing the level of productivity and innovation, while at the same time the low efficiency of economic entities, through bankruptcy, eliminates them from the market. In addition, the economic policy principles of the Ordo Liberal concepts meet the requirements of theoretical coherence and feasibility. The aim of this article is to present a competitive economic governance developed within the framework of ordo liberal theories as an appropriate approach to be applied to improving the competitiveness of the economy and the challenges of the new era. The first part of the article will present the approach to competitiveness, then the introduction to ordo liberalism as the theoretical basis for competitive economic governance, and the final part will specify the principles of competitive economic governance that serve / lead to the achievement of higher economic competitiveness. The thesis of the article is that the basis for achieving a high growth in competitiveness is to strengthen the forces of competition by creating and safeguarding the conditions for the development of economic freedom.
Keywords: Ordo liberalism; competitive economic governance; the phenomenon of misappropriation; principles that constitute economic governance; cost transfer; economic competitiveness; economic freedom; economic viability; innovation.